Design Related Investigations for Media Access Control Protocol Service Schemes in Wavelength Division Multiplexed All Optical Networks - Selvadurai, Selvakennedy (1999)
All-optical networks (AON) are emerging through the technological advancement of various optical components, and promise to provide almost unlimited bandwidth. To realise true network utilisation, software solutions are required. An active area of research is media access control (MAC) protocol. This protocol should address the multiple channels by wavelength division mutiplexing (WDM) and bandwidth management. Token-passing (TP) is one such protocol, and is adopted due to its simplicity and collisionless nature. Previously, this protocol has been analysed for a single traffic type. However, such a study may not substantiate the protocol's acceptance in the AON design. As multiple traffic types hog the network through the introduction multimedia services and Internet, the MAC protocol should support this traffic. Four different priority schemes are proposed for TP protocol extension, and classified as static and dynamic schemes. Priority assignments are a priori in static scheme, whereas in the other scheme, priority reassignments are carried out dynamically. Three different versions of dynamic schemes are proposed. The schemes are investigated for performance through analytical modelling and simulations. The semi-Markov process (SMP) modelling approach is extended for the analyses of these cases. In this technique, the behaviour of a typical access node needs to be considered. The analytical results are compared with the simulation results. The deviations of the results are within the acceptable limits, indicating the applicability ofthe model in all-optical environment. It is seen that the static scheme offers higher priority traffic better delay and packet loss performance. Thus, this scheme can be used beneficially in hard real-time systems, where knowledge of priority is a priori. The dynamic priority scheme-l is more suitable for the environments where the lower priority traffic is near real-time traffic and loss sensitive too. For such a scheme, a larger buffer with smaller threshold limits resulted in improved performance. The dynamic scheme-2 and 3 can be employed to offer equal treatment for the different traffic types, and more beneficial in future AONs. These schemes are also compared in their performance to offer constant QoS level. New parameters to facilitate the comparison are proposed. It is observed that the dynamic scheme-l outperforms the other schemes, and these QoS parameters can be used for such QoS analysis. It is concluded that the research can benefit the design of the protocol and its service schemes needed in AON system and its applications.